At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Replace the values of [tex][tex]$m$[/tex][/tex] and [tex][tex]$n$[/tex][/tex] to show the solutions of this equation.

[tex]\[ x^2 + 6x - 5 = 0 \][/tex]

[tex]\[ x = m \pm n \][/tex]

Enter the correct answer in the box.


Sagot :

To solve the quadratic equation [tex]\( x^2 + 6x - 5 = 0 \)[/tex], we follow the standard steps used for solving quadratic equations of the form [tex]\( ax^2 + bx + c = 0 \)[/tex].

1. Identify the coefficients:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = 6 \)[/tex]
- [tex]\( c = -5 \)[/tex]

2. Calculate the discriminant using the formula [tex]\(\Delta = b^2 - 4ac\)[/tex]:
[tex]\[ \Delta = 6^2 - 4 \times 1 \times -5 = 36 + 20 = 56 \][/tex]

3. Find the two solutions of the quadratic equation using the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{\Delta}}{2a} \)[/tex]:

- For the positive root [tex]\(\left(x_1\right)\)[/tex]:
[tex]\[ x_1 = \frac{-b + \sqrt{\Delta}}{2a} = \frac{-6 + \sqrt{56}}{2 \times 1} = \frac{-6 + \sqrt{56}}{2} \][/tex]
On calculating the above value, we get:
[tex]\[ x_1 \approx 0.7416573867739413 \][/tex]

- For the negative root [tex]\(\left(x_2\right)\)[/tex]:
[tex]\[ x_2 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{-6 - \sqrt{56}}{2 \times 1} = \frac{-6 - \sqrt{56}}{2} \][/tex]
On calculating the above value, we get:
[tex]\[ x_2 \approx -6.741657386773941 \][/tex]

Thus, the solutions to the quadratic equation [tex]\( x^2 + 6x - 5 = 0 \)[/tex] are:

[tex]\[ x_1 \approx 0.7416573867739413 \quad \text{and} \quad x_2 \approx -6.741657386773941 \][/tex]

So the solutions can be written as:

[tex]\[ x = m \pm n \][/tex]

Where [tex]\( m \)[/tex] and [tex]\( n \)[/tex] correspond to the approximate values:
- [tex]\( x = 0.7416573867739413 \)[/tex]
- [tex]\( x = -6.741657386773941 \)[/tex]

Replacing these values, the solutions of the equation [tex]\(x^2 + 6x - 5 = 0 \)[/tex] are:
[tex]\[ x = 0.7416573867739413 \quad \text{and} \quad x = -6.741657386773941 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.